TINJAUAN MUSIKAL MATERI LOMBA KARAWITAN TINGKAT SEKOLAH DASAR 01 SURAKARTA - Isti Kurniatun (Gelar : Jurnal Seni Budaya, 2010)
Education, Youth and Sport Service of Surakarta holds karawitan festival for Elementary Schools once a year. The problem of the festival is that the pieces of the festival does not match with the  physical and psychic competence of children. The pieces of the festival (instrumentation and vocalization) is more suitable for adults than children. Beside that, the gendhing (melody) and  larasan (pitch) do not come up to a child's competence. This becomes a problem for the children, teachers and instructors. This research aims at finding out the form and garap of the matter of karawitan festival for Elementary Schools and how the pieces were arranged. In addition, it aims at offering a solution that can be taken into consideration in arranging the future pieces of the  festival in order that the pieces are in accordance with children's physical and psychic need and competence. The approach used in this research is a musical, psychological, and social one. The  main objective of the art festival in "Art Week" in Surakarta is to encourage the growth of the spirit of nationalism that loves their own national culture. The target of the program is the students of  elementary schools and senior high schools. To attain the objectives, concrete and certain steps are needed not only limited to art events but also art appreciation focusing on traditional art like drama, poetry, vocal, dances, and music including karawitan.Key words: musical, festival, karawitan, children, Elementary Schools.